2010
DOI: 10.1088/2041-8205/721/2/l126
|View full text |Cite
|
Sign up to set email alerts
|

An Apparently Extended Infrared Counterpart to 1e 1740.7–2942

Abstract: We present the results of a revised search for the near-infrared counterpart to the microquasar 1E 1740.7−2942, which has eluded identification despite the many years elapsed since its discovery. By taking into account new astrometric information, we have been successful to identify a single near-infrared source, with apparent non-stellar morphology, whose position agrees well with that of the microquasar X-ray and radio-emitting core at the subarcsecond level. The possible implications of this finding with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…1 we provide a general view of the 1E 1740.7−2942 field for illustrative purposes. This figure shows the microquasar location in a complex region rich in extended radio emission (Martí et al 2010). Other large-scale filamentary features, such as G359.10−00.20 also known as the Galactic center Snake (Yusef-Zadeh et al 1984) are present as well.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…1 we provide a general view of the 1E 1740.7−2942 field for illustrative purposes. This figure shows the microquasar location in a complex region rich in extended radio emission (Martí et al 2010). Other large-scale filamentary features, such as G359.10−00.20 also known as the Galactic center Snake (Yusef-Zadeh et al 1984) are present as well.…”
Section: Introductionmentioning
confidence: 80%
“…In particular, the absolute magnitude of the infrared counterpart candidate proposed in Martí et al (2010) should be revised to K s = −3.0. At 5 kpc, this would be consistent with an early-type B star on the main sequence or a middle-KIII giant star.…”
Section: Implications Of the Precession Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…There is, until now, no optical or infrared counterpart confirmed for E-mail: paulo.stecchini@inpe.br 1E 1740.7−2942 -which is usually attributed to the high galactic extinction towards the GC at these wavelengths (see, e.g., Gallo & Fender 2002). In one of the most recent attempts, Martí et al (2010) have successfully identified a single near-infrared source towards the system's location. The study suggested two hypotheses to explain the counterpart candidate detected: an Active Galactic Nucleus projected along the line of sight of the system or a black hole highmass X-ray binary.…”
Section: Introductionmentioning
confidence: 99%